Productive Verbal Interactions in Classrooms With Children From Different Socioeconomic Backgrounds: An Empirical Study in Chilean Schools - Muñoz-Hurtado, Javiera (Psykhe, 2020)
The purpose of this study was to explore the characteristics of classroom talk in 2 Chilean schools located in Santiago. Both schools, which were purposively selected, have a shared interest in dialogue, but serve students from different socioeconomic status [SES] backgrounds. Observations of naturally occurring verbal interactions in 3 consecutive science lessons were conducted in 4th grade classrooms. Interactions between the teacher and the whole class were examined adopting a sociocultural discourse analysis approach, using both quantitative and qualitative data. Results show that verbal interactions with students from a lower SES background tend to be more concrete and adult-dependent. Talk in this classroom was characterised by a predominance of closed questions; however, this is not a sign of less productive interaction, but evidence of a different way of using language in academic interactions taking place in more vulnerable contexts. It is suggested that teachers and researchers need to acknowledge these linguistic characteristics of students from lower SES backgrounds in order to promote meaningful classroom talk.